Politics, Religion and Gender Framing and Regulating the Veil - Rosenberger, Sieglinde; Sauer, Birgit (Routledge Studies in Religion and Politics, 2012)
Heated debates about Muslim women's veiling practices have regularly attracted the attention of European policymakers over the last decade. The headscarf has been both vehemently contested by national and/or regional governments, political parties and public intellectuals and passionately defended by veil wearing women and their supporters. Systematically applying a comparative perspective, this book addresses the question of why the headscarf tantalises and causes such controversy over issues about religious pluralism, secularism, neutrality of the state, gender oppression, citizenship, migration, and multiculturalism. Seeking also to establish why the issue has become part of the disciplinary practices of some European countries but not of others, this work brings together an important collection of interpretative research regarding the current debates on the veil in Europe, offering an interdisciplinary scope and European-wide setting. Brought together through a common research methodology, the contributors focus on the different religious, political and cultural meanings of the veiling issue across eight countries and develop a comparative explanation of veiling regimes. This work will be of great interest to students and scholars of religion & politics, gender studies and multiculturalism.